Identificación de macronutrientes, micronutrientes y microorganismos en el bocashi elaborado en base a residuos ruminales. - Yong Lescano, Jean Jazmany (2020)
The use of organic amendments such as bocashi are well known worldwide, however, research is not very precise on their nutritional content and little reference is made to the existing microbial load. The present investigation consisted in the elaboration of bocashi to identify the chemical and microbiological properties, the C / N ratio; also the temperature, humidity and pH for 15 days. For this purpose, the method was applied completely at random with four treatments in six repetitions. All treatments presented N, P, K, Ca, Ca, Br, Zn, Co, Fe, Mg, S and MO. Likewise, Pseudomonas bacteria, Aspergillus niger fungi, actinomycetes and yeasts were registered. In the pH variable, treatments 1; two; and 3 do not differ statistically, the highest being T1 with a value of 5.43, however, all the mentioned treatments differ from the control that presents the lowest average of 4.84. In the humidity variable there are no statistical differences between the treatments and the control, the highest percentage being 51.81% registered in T1; the highest temperature was presented in the control with 45.95ºC degrees centigrade followed by treatment 3 with an average of 45.83ºC. All the treatments presented the carbon / nitrogen ratio, the.highest being the control with 23.8% C / N; followed by treatment 2 with 12.4% C / N. The production of bocashi from ruminal residues associated with other materials constitutes a compost alternative. Keywords: temperature, humidity, pH, yeasts, ruminals, agroecosystem